2011
DOI: 10.5423/ppj.2011.27.2.120
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Alternaria alternata as a Causal Agent for Leaf Blight in Syringa Species

Abstract: While many isolates of Alternaria alternata are common saprophytes on trees and shrubs, this study clearly demonstrated that A. alternata is a primary pathogen in lilac (Syringa sp.), causing a leaf-blight that affects different Syringa species. Isolates of Alternaria sp. were collected from leaf blight samples of lilacs in the field. The internal transcribed spacer (ITS) region and morphological characterization were used to identify lilac blight pathogen. Based on 100% ITS nucleotide sequence identities to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…The ribosomal genes and their ITS regions have been extensively used for distinguishing and naming of the species (Yang et al 2020), along with the study of genetic diversity (Ghosh et al 2019;Turzhanova et al 2020), phylogenetic relationship (Ozkilinc et al 2018;Liu et al 2019;Tao et al 2019), and taxonomic studies (Mahmoudi et al 2017;Poursafar et al 2018). In fungi, ITS region is used in species identification and phylogenetic studies of closely related species (Mmbaga et al 2011). Since there is a higher degree of variation in ITS gene sequence, it has been extensively applied in molecular taxonomy to discriminate at species levels or sometimes even within species (Al Ghafri et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The ribosomal genes and their ITS regions have been extensively used for distinguishing and naming of the species (Yang et al 2020), along with the study of genetic diversity (Ghosh et al 2019;Turzhanova et al 2020), phylogenetic relationship (Ozkilinc et al 2018;Liu et al 2019;Tao et al 2019), and taxonomic studies (Mahmoudi et al 2017;Poursafar et al 2018). In fungi, ITS region is used in species identification and phylogenetic studies of closely related species (Mmbaga et al 2011). Since there is a higher degree of variation in ITS gene sequence, it has been extensively applied in molecular taxonomy to discriminate at species levels or sometimes even within species (Al Ghafri et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Both Alternaria alternata and A. solani can cause early blight on potatoes in the world 26 30 31 32 33 . A. alternata produces densely turfy colonies in dark grey to black brown color on PDA plates.…”
mentioning
confidence: 99%
“…The ITS sequencing was a rapid and reliable method to identify different species of date palm fungal contamination; many published reports have proved the effectiveness and reliability of ITS products as a tool of fungal discrimination including the species of Aspergillus, Alternaria and Penicillium (Henry et al, 2000;Konstantinova et al, 2002;Martinez-Culebras and Ramon, 2007;Diguta et al, 2011;Mmbaga et al, 2011;Pashley et al, 2012). The digestion with restriction endonucleases EcoRI and SmaI following the ITS amplification, indicated that both restriction endonucleases were sufficient to recognize the fungal contaminants (Aspergillus, Alternaria and Penicillium) of date palm tissue culture at species level.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the isolated fungi belonged to the B Type pattern, with an exception of species A. calvatus which belonged to the C Type pattern with three fragments after digestion with SmaI. The ITS-RFLP procedure is widely used as a rapid and reliable technique for fungal identification, especially for the close taxa within the genera of fungi such as Aspergillus, Alternaria and Penicillium (Martinez-Culebras and Ramon, 2007;Diguta et al, 2011;Mmbaga et al, 2011).…”
Section: Discussionmentioning
confidence: 99%